On competition and the strategic management of intellectual property in oligopoly - Jos Jansen (Max Planck Institute for Research on Collective Goods, 2009)
An innovative firm chooses strategically whether to patent its process innovation or rely on secrecy. By doing so, the firm manages its rival's beliefs about the size of the innovation, and affects the incentives in the product market. Different measures of competitive pressure in the product market have different effects on the equilibrium patenting choices of an innovative firm with unknown costs and probabilistic patent validity. Increasing the number of firms (degree of product substitutability) gives a smaller (greater) patenting incentive. Switching from Bertrand to Cournot competition gives a smaller (greater) patenting incentive if patent protection is weak (strong).
Keywords: D82; L13; O31; O32; 330; Bertrand and Cournot competition; oligopoly; product differentiation; entry; asymmetric information; strategic disclosure; stochastic patent; trade secret; process innovation; imitation; Innovation; Patent; Oligopol; Imitationswettbewerb; Produktdifferenzierung; Informationsverhalten; Spieltheorie; Theorie